The Conceptual Construction of the Interaction Process in the Foreign Language Classroom - Mello, Heliana; Dutra, Deise (The ESPecialist, 2012)
In this paper we describe and discuss data gathered through a research project which focuses on pre-service teacher reflective practices (Dutra & Mello, 2001). We take a contrastive perspective in our analysis, as we look at teachers’ and students’ conceptual schemas, which emerge from discourse samples collected at five reflective sessions and questionnaires. The conclusions drawn from this study indicate that a collective construction of roles in the classroom scene would enhance learning in the FL/L2 environment.